Structure and Mechanism of Glycine Receptor Elucidated by Cryo-Electron Microscopy - Zhu, Hongtao (Frontiers in Pharmacology, 2022)
Glycine receptors (GlyRs) are pentameric ion channels that mediate fast inhibitory neurotransmission. GlyRs are found in the central nervous system including the spinal cord, brain stem and cerebellum, as well as in the retina, sperm, macrophages, hippocampus, cochlea and liver. Due to their crucial roles in counter-balancing excitatory signals and pain signal transmission, GlyR dysfunction can lead to severe diseases and as a result, compounds that modify GlyR activity may have tremendous therapeutic potential. Despite this potential, the development of GlyR-specific small-molecule ligands is lacking. Over the past few years, high resolution structures of both homomeric and heteromeric GlyRs structures in various conformations have provided unprecedented details defining the pharmacology of ligand binding, subunit composition, and mechanisms of channel gating. These high-quality structures will undoubtedly help with the development of GlyR-targeted therapies.